Gambaran Life Skills dan Perkembangan Tahapan Karir pada Siswa Autism Spectrum Disorder di Sekolah Y - Natascha Cristina; Penny Handayani (Jurnal Ilmiah Psikologi MIND SET, 2023)
The number of people with autism in Indonesia has reached 2.4 million people. Students with Autism Spectrum Disorder (ASD) have limitations in social functioning, as well as the ability to communicate and behave. These limitations are the main influencing factors in choosing a career to pursue. Given this, researchers wanted to see an overview of life skills and career development stages in ASD students at School Y. This research was conducted using a mixed methods convergent parallel design. Data collection was carried out through interviews (qualitative) and behavior checklist (quantitative). The number of participants was five ASD students who had studied for at least three years at School Y. Given the limitations of the ASD students, information was collected from teachers (first informant) and caregivers of each student (second informant). The data analysis strategy used in this study is thematic analysis and descriptive statistics. The results showed that the five ASD students at School Y had quite good mastery of life skills in personal and social skills but were still limited to academic and vocational skills. In terms of the development of career stages, three students are already at a career stage appropriate to their age. The support of parents and teachers in helping ASD students identify their interests, talents, strengths, and weaknesses is very instrumental for better career planning skills.